2022
DOI: 10.1186/s13287-022-02751-0
|View full text |Cite
|
Sign up to set email alerts
|

Current status of clinical trials assessing mesenchymal stem cell therapy for graft versus host disease: a systematic review

Abstract: Background Graft-versus-host disease (GVHD) is a common fatal complication of hematopoietic stem cell transplantation (HSCT), where steroids are used as a treatment option. However, there are currently no second-line treatments for patients that develop steroid-resistance (SR). Mesenchymal stem cells (MSCs) have immunomodulatory functions and can exert immunosuppressive effects on the inflammatory microenvironment. A large number of in vitro experiments have confirmed that MSCs can significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 109 publications
2
30
0
Order By: Relevance
“…Accordingly, the more models in vivo are essential and very important to be able to translate the achievements to human medicine from one health perspective. 66 , 67 …”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the more models in vivo are essential and very important to be able to translate the achievements to human medicine from one health perspective. 66 , 67 …”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that the cell source chosen is influenced by a variety of patient- and diagnosis-related characteristics, as well as the availability of appropriately matched donors, leaving the question of which cell source is superior or has more benefits unanswered[ 39 ]. The recent systematic review of clinical trials[ 40 ] also reported the use of the BM HSCs as the main source by IV transplantation. Wu et al [ 20 ] reported transplantation of a pool of human nucleated cells, Huang et al [ 10 ] and Lim et al [ 21 ] reported the use of a mononuclear cell pool without any cell selection process, and Fernández-García et al [ 17 ] used LSK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding these methodological limitations in the preclinical research, clinical trials have reported significant results related to the increase in engraftment and survival rate through HSC and MSC cotransplantation. The recent systematic reviews of clinical trials[ 4 , 40 , 58 ] have shown that the more homogeneous the MSCs are in terms of the donor, source, extraction method, culture, and other aspects, the better is their efficacy and potentially, the less treatment dose required, and therefore the less likely they are cause adverse events. These clinical trial reviews showed that use of allogeneic MSC cotransplantation in allo-HSC, in phase II, or autogenic sources of MSC in phases I and II during cotransplantation of HSC and MSC increased the survival rate in clinical trials compared with other animal studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 500 clinical research on MSC is underway in the world for various target diseases, including rheumatoid arthritis, systemic lupus erythematosus, Crohn’s disease, myocardial infarction, Parkinson’s disease, spinal cord injury, osteoarthritis, and graft-versus-host disease (GVHD) [ 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 ]. MSCs other than those derived from bone marrow are also being clinically applied.…”
Section: Clinical Use Of Msc-evsmentioning
confidence: 99%